What role for the home learning environment and parenting in reducing the socioeconomic gradient in child development? Findings from the Millennium Cohort Study. Issue 9 (12th June 2011) - Kelly, Y; Sacker, A; Del Bono, E; Francesconi, M; Marmot, M
Abstract : Background: Early child health and development (ECD) is important for health in later life. Objectives were to (1) examine the extent of socioeconomic inequality in markers of ECD at ages 3 and 5 years; (2) examine whether the ECD–income gap widens between these ages; (3) assess the contribution of the home learning environment, family routines and psychosocial environment to observed inequalities in ECD. Methods: Data on socioemotional difficulties, and tests of cognitive ability in 3-year-old (n=15 382) and 5-year-old (n=15 042) children from the UK Millennium Cohort Study were used. Results: Children in the highest income group were less likely to have socioemotional difficulties compared with those in the lowest income group at 3 and 5 years (2.4% vs 16.4% and 2.0% vs 15.9%, respectively) and had higher mean scores: age 3 'school readiness' 114 versus 99; verbal ability 54 versus 48, and age 5: verbal ability 60 versus 51, non-verbal ability 58 versus 54 and spatial ability 54 versus 48 (all p<0.001). The income gap in verbal ability scores widened between ages 3 and 5 (Wald test, p=0.04). Statistical adjustment for markers of home learning, family routines and psychosocial environments did more to explain the income gap in socioemotional difficulties than in cognitive test scores. Conclusion: Our results suggest that relationships between family income and markers of ECD are amenable to change. The role of home learning, family routines and psychosocial environmental factors are potentially important in closing income gaps in ECD.